Medicinal Signaling Cells Metabolite Oral Based as a Potential Biocompatible Biomaterial Accelerating Oral Ulcer Healing (In Vitro Study) - Nugraha, Alexander Patera; Purwati; Susilowati, Helen; Hendrianto, Eryk; Karsari, Deya; Ertanti, Nora; Dinaryanti, Aristika; Ihsan, Igo Syaiful; Narmada, Ida Bagus; Ernawati, Diah Savitri; Rantam, Fedik Abdul (European Journal of Dentistry, 2019)
Objective Medicinal signaling cells metabolite (MSCM) is often considered medical waste even though it contains abundant growth factors, and advantageous micro- and macromolecules that can accelerate healing in oral ulcer.The purpose of this experimental laboratory study was to analyze the biocompatibility and potential of MSCM, (oral based) to accelerate healing in oral ulcer (in vitro).Materials and Methods MSCM (oral based) was obtained by mixing 10 mL of MSCM and 2% of carboxymethyl cellulose sodium. 3- (4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (or MTT assay) was obtained using human gingival somatic cell culture to examine cell viability treated with MSCM (oral based). Fourier transform infrared spectroscopy was performed to know the functional structure and composition of MSCM (oral based). To know the elemental composition of MSCM (oral based), energy-dispersive X-ray analysis was performed. Scratch test was performed to know the ability of MSCM (oral based) to increase human somatic cell proliferation.Results MSCM (oral based) has good cell viability. MSCM (oral based) administration accelerated the proliferation of human somatic cell culture after 12-hours in vitro. MSCM (oral based) has carboxylic acids and derivatives chemical bond. MSCM (oral based) mostly contained carbon and potassium but did not contain heavy metal substances.Conclusions MSCM (oral based) has a biocompatible and potential ability to accelerate healing in oral ulcer in vitro. It would be useful in daily clinical practice in treating traumatic oral ulcer.
Keywords: medicinal signaling cells; wound healing; biomaterial; metabolite; biocompatibility